BERADAPTASI DENGAN PELEMAHAN EKONOMI GLOBAL DI INDONESIA DENGAN MEMANFAATKAN INSTRUMEN FISKAL DAN MONETER - Al-Mujaddid, Toriq Furqon; Suwito Suwito (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The study evaluates the efficiency of fiscal and monetary measures mitigating the worldwide economic downturn impacted Indonesia's economy. During the crisis, Indonesia faced challenges such as trade disruptions, decreased export demand, and financial sector experiences liquidity issues. Bank Indonesia implemented accommodative monetary policies, including interest rate adjustments, to stabilize financial markets and support economic recovery. The Indonesian government pursued an expansive fiscal policy, increasing government spending on infrastructure and social welfare programs to stimulate economic activity and mitigate social unrest. Tax incentives and relief measures were introduced to support businesses and stimulate investment, while targeted subsidies were provided to specific industries. Despite challenges such as fiscal constraints and external shocks, these policy measures contributed to reducing the crisis's impact, promoting economic resilience, and fostering sustainable development in Indonesia. Continuous evaluation and adaptation of policy frameworks are recommended to address emerging challenges effectively in the future.